Towards a Model of Psychological Well-Being. the Role of Socioeconomic Status and Satisfaction with Income in Chile - Vera-Villarroel, P; Torres-Ortega, J; Celis-Atenas, K; Oyanedel-Sepulveda, J; Contreras-Ramirez, D; Lillo-Vidal, S (Pontificia Universidad Javeriana, 2015)
Association between indexes of socioeconomic status, satisfaction with income and status, and psychological well-being (PWB) was examined in a representative sample of Chileans. Results confirm a positive association between socioeconomic status and satisfaction with income and status and PWB. Associations were stronger with PWB facets related to relational, control and self-esteem processes, and weaker with purpose of life, growth and autonomy. Structural equation modeling confirmed a direct significant coefficient of socioeconomic status on PWB, as well as an indirect significant path through satisfaction with income and status. Control for satisfaction with socioeconomic status and purchase power reduced but did not eliminate the effect of socioeconomic status on PWB. Results are consistent with a direct effect model of socio-structural position on well-being, but also with the relevance of satisfaction with social position as an appraisal process to indicate high psychological well-being.